Unlocking Coldplay’s Lyric Paradise and Higher Power: An Experiential Meta-function Analysis for Enhanced Communication - Kaunang, Tania Caren; Simanjuntak, Debora Chaterin (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The aim of the research is to understand how the lyrics in these songs convey emotions and ideas. Meta-function analysis provides insight into how language is used in real-world communication. This study focuses on analyzing the songs ‘Paradise’ and Higher Power’ by the band Coldplay. It utilizes a method called Experiential Meta-Function Analysis (EMA) to dissect how the lyrics of these songs express and convey ideas. Through a careful analysis, common themes in their songs, such as societal issues, spiritual sentiments, and emotional challenges, are identified. The analysis reveals a collective count of 21 clauses distributed in "Paradise" with 15 independent clauses and 6 dependent clauses and there is a collective amount of 32 clauses in "Higher Power," with 25 independent clauses and 7 dependent clauses. From the table above, it is evident that there are a total of 51 processes across the songs. Notably, material processes constitute the majority, accounting for 47.6% in "Paradise" and 36.6% in "Higher Power". Relational processes rank second, representing 9.2% in "Paradise" and 33.3% in "Higher Power". Existential processes are the least utilized in both lyrics. Overall, the strategic use of processes in both "Paradise" and "Higher Power" allows Coldplay to effectively convey their messages while evoking profound emotional responses from listeners. Through a combination of actions, states of being, and sensory experiences, the songs create immersive narratives that resonate deeply with audiences, encouraging introspection, connection, and empowerment. Ultimately, the research highlights the symbiotic relationship between language and music, emphasizing their collective ability to evoke profound emotional responses and foster understanding. This investigation contributes to a deeper comprehension of why popular music holds significant meaning for listeners.